Problems of Regional Identification of Production Losses from the COVID-19 Pandemic and their Solutions in the System of International Statistical Standards - A. B. Dukhon; O. I. Obraztsova; N. D. Epshtein (Статистика и экономика)
Purpose of research. Analysis of the information capabilities of the methodology of the UN national accounts system as amended in 2008 to solve the problems of regional identification of production losses from the COVID-19 pandemic. The coronavirus infection pandemic caused a decline in production in almost all types of economic activity. The Russian government has identified a strategy to counter the extraordinary economic crisis triggered by the pandemic. The range of addressees of anti-crisis measures of the executive branch in the sectors of producers is determined, at the federal and regional levels, according to the main type of activity declared during registration, in accordance with the approved list of codes of the Russian National Classifier of Types of Economic Activity for the types of activities that are most affected by the pandemic and self-isolation regime. The approved list of such types of activities over the past 2 months has been repeatedly adjusted by the Government of the Russian Federation, taking into account the recommendations of experts and proposals of business-structures, in order to ensure the highest efficiency and targeted state support for manufacturers. Ensuring targeted state support during optimization of the federal resources distribution between regions - is an urgent task that requires accurate regional identification of production losses from the COVID-19 pandemic. However, the solution of this problem is significantly difficult in relation to the activities of multi-regional producers - enterprises that carry out production simultaneously in several territories of the Russian Federation. This is due to the characteristics of the organization system of statistical accounting of resources and production results in the enterprise sector. The paper considers the possibility of assessing the gross value added at the regional level for the aggregate of local producing units, grouped by the type of economic activity, based on methodological principles harmonized with international standards and guidelines of the current version of the national and regional accounts system and provided with resources of official (state and administrative) statistics of the Russian Federation.Materials and methods. The research information base was made up of official statistical sources: metadata and international statistics guidelines in the field of subnational accounting, methodological provisions and an album of ROSSTAT forms, as well as methodological materials of administrative statistics of the Federal Tax Service (FTS) and the Social Insurance Fund. The methodological basis of the study was the United Nations system of national accounts as amended in 2008, including the European system of regional accounts as amended in 2010.Results. The paper analyzes the principles of the European system of regional accounts, which are useful to use in Russian statistics for adequate accounting of the activities’ results of multiregional enterprises at the place of actual production and methodological approaches to assessing the number of such enterprises and the results of their production at the subnational level are proposed. The results obtained will allow us to estimate the loss of multiregional enterprises of different types of activity from the decline in production as a result of the ban on interregional relations during the COVID-19 pandemic, in order to determine the recipients of state support for enterprises in the regions. In particular, the proposed indicator for reducing the regional GVA for the most affected by the quarantine measures activities can be used as a condition for the allocation of funds as part of overcoming the consequences of the pandemic. The application of the proposed methodology in calculating the gross value added at the place of actual production for the aggregate of geographically separate divisions of multiregional enterprises will increase the targeting and effectiveness of state support for enterprises and entrepreneurs affected by the consequences of the spread of coronavirus infection, and will optimize the distribution of federal resources between regions, which is a prerequisite for successful overcoming “coronacrisis”.